Intraosseous Hemangioma of the Middle Turbinate Misdiagnosed As a Nasal Polyp - Tae Hoon Kim; Eun Jung Lim; Jun-Ki Lee; Jin Gul Lee; Man-Hoon Han (Case Reports in Otolaryngology)
Intraosseous hemangiomas account for 1% of all bone tumors and primarily originate from the vertebral column and skull bones. However, intraosseous hemangiomas of the nasal cavity are extremely rare. Here, we report a case of intraosseous hemangioma with a cavernous pattern arising from the middle turbinate that was preoperatively misdiagnosed as chronic rhinosinusitis with polyps. Except for nasal obstruction, there were no specific rhinologic symptoms. The tumor was excised en bloc by the endoscopic endonasal approach without preoperative embolization.